PROANTHOCYANIDIN-PLGA NANOPARTICLE INFUSED CALCIUM HYDROXIDE SEALER: ADVANCING MATERIAL PERFORMANCE AND CLINICAL STABILITY IN ENDODONTICS - SADANANDA, VANDANA; S., GOWRISH; CHARYULU, R. NARAYANA; HEGDE, MITHRA N. (International Journal of Applied Pharmaceutics, 2025)
Objective: The study presents a novel calcium hydroxide-based endodontic sealer infused with proanthocyanidin nanoparticles (PAC-NPs) encapsulated in poly(actic-co-glycolic acid) (PLGA), designed to enhance critical clinical properties and overcome limitations of traditional sealers. Methods: The sealer's formulation was evaluated for flow, setting time, solubility, dimensional stability, and pH, adhering to ISO 6876:2012 and ANSI/ADA standards 57. The incorporation of PAC-PLGA and calcium hydroxide nanoparticles was analyzed using Attenuated Total Reflectance-Fourier Transform Infrared Spectroscopy (ATR-FTIR) to confirm chemical interactions and functional integration. Results: The sealer exhibited exceptional flow properties (23.78 mm), a balanced setting profile (initial: 65 min; final: 810 min), and low solubility (0.825%), ensuring durability and clinical reliability. Dimensional stability remained within ISO limits (0.417% over 30 days). The sealer maintained a highly alkaline environment (pH 12.3 initially, stabilizing at 10.6 over four weeks), crucial for antimicrobial activity and healing. ATR-FTIR confirmed the stable incorporation of PAC-PLGA NPs, potentially offering antioxidant and collagen-stabilizing benefits. Conclusion: This novel formulation demonstrates significant improvements in critical clinical parameters, offering a durable and bioactive alternative to traditional calcium hydroxide sealers. While no immediate limitations were observed, further in vivo assessments are recommended to evaluate its long-term sealing efficacy, dentine preservation, and periapical healing outcomes.